Low-barrier interface via noble metal induction for external energy-free ppb-level room-temperature formaldehyde sensing - Ziming Yang; Jiangnan Chang; Ying Qiao; Sitao Lv; Leqi Zhang; Yifei Fan; You Wu; Ruofei Lu; Hao Li; Yanan Guo; Patrick J. French; Jun Yin; et al. (Chemical Engineering Journal, 2026)

Tandem catalytic upgrading of cow manure pyrolysis vapors by Beta zeolite and nitrogen-doped activated carbon dual catalysts prepared from coal gasification fine slag to produce light aromatic hydrocarbons - Ruofei Wu; Peng Lv; Xuanxuan He; Yonghui Bai; Jiaofei Wang; Juntao Wei; Weiguang Su; Xudong Song; Guangsuo Yu (Journal of Environmental Chemical Engineering, 2025)

High dielectric sulfonyl-containing polyimide binders optimize the long-term stability and safety of NCM811 lithium-ion batteries at high voltages - Lin Chen; Dandan Yang; Junhao Xin; Xiaowei Zhou; Yuchen Zhang; Zixin Lv; Tiegen Guo; Qinghai Chen; Ruofei Gao; Ying Wang; Ning Wang; Shuanyan Kang; et al. (Chemical Engineering Journal, 2025)

Aromatics production from relay catalytic pyrolysis of cow manure using Ru/C and ZSM-5 dual catalysts synthesized from coal gasification fine slag - Ruofei Wu; Peng Lv; Bin Liu; Yonghui Bai; Jiaofei Wang; Juntao Wei; Weiguang Su; Guangyu Xu; Weina Bao; Guangsuo Yu (Journal of Environmental Management, 2023)

Catalytic upgrading of cow manure pyrolysis vapors over zeolite/carbon composites prepared from coal gasification fine slag: High quality bio-oil obtaining and mechanism investigation - Ruofei Wu; Peng Lv; Jiaofei Wang; Yonghui Bai; Juntao Wei; Xudong Song; Weiguang Su; Guangsuo Yu (Fuel, 2023)

5300‐Year‐old soil carbon is less primed than young soil organic matter - Jiao Su; Haiyang Zhang; Xingguo Han; Ruofei Lv; Li Liu; Yong Jiang; Hui Li; Yakov Kuzyakov; Cunzheng Wei (Global Change Biology, 2023)
Soils harbor more than three times as much carbon (C) as the atmosphere, a large fraction of which (stable organic matter) serves as the most important global C reservoir due to its long residence time. Litter and root inputs bring fresh organic matter (FOM) into the soil and accelerate the turnover of stable C pools, and this phenomenon is termed the “priming effect” (PE). Compared with knowledge about labile soil C pools, very little is known about the vulnerability of stable C to priming. Using two soils that substantially differed in age (500 and 5300 years before present) and in the degree of chemical recalcitrance and physical protection of soil organic matter (SOM), we showed that leaf litter amendment primed 264% more organic C from the young SOM than from the old soil with very stable C. Hierarchical partitioning analysis confirmed that SOM stability, reflected mainly by available C and aggregate protection of SOM, is the most important predictor of leaf litter‐induced PE. The addition of complex FOM (i.e., leaf litter) caused a higher bacterial oligotroph/copiotroph ( K ‐/ r ‐strategists) ratio, leading to a PE that was 583% and 126% greater than when simple FOM (i.e., glucose) was added to the young and old soils, respectively. This implies that the PE intensity depends on the chemical similarity between the primer (here FOM) and SOM. Nitrogen (N) mining existed when N and simple FOM were added (i.e., Glucose+N), and N addition raised the leaf litter‐induced PE in the old soil that had low N availability, which was well explained by the microbial stoichiometry. In conclusion, the PE induced by FOM inputs strongly decreases with increasing SOM stability. However, the contribution of stable SOM to CO 2 efflux cannot be disregarded due to its huge pool size.

Accelerated removal of Sudan dye by Shewanella oneidensis MR-1 in the presence of quinones and humic acids - Guangfei Liu; Jiti Zhou; Qiuyan Ji; Jing Wang; Ruofei Jin; Hong Lv (World Journal of Microbiology and Biotechnology, 2013)